Fables of abundance : a cultural history of advertising in America - Lears, T. J. Jackson, 1947- ([New York] : Basic Books, 1994)
The book explores the ways that advertising collaborated with other cultural institutions to produce what have become the dominant aspirations, anxieties, and even notions of personal identity in the twentieth-century United States. Moving from the carnivals and market fairs of Renaissance Europe to the traveling peddlers of nineteenth-century America, Jackson Lears shows how early advertisers encouraged a new kind of magical thinking, detached from religious traditions and geared to an emerging market society. While patent medicine advertising's promise of magical self-transformation and exotic sensuality posed challenges to moral standards, advertisers themselves eventually sought to contain the subversive potential of this promise even as they continued to conjure it up.
Pt. I. The Reconfiguration of Wealth: From Fecund Earth to Efficient Factory. 1. The Lyric of Plenty. 2. The Modernization of Magic. 3. The Stabilization of Sorcery. 4. The Disembodiment of Abundance -- Pt. II. The Containment of Carnival: Advertising and American Social Values from the Patent Medicine Era to the Consolidation of Corporate Power. 5. The Merger of Intimacy and Publicity. 6. The Perfectionist Project. 7. The New Basis of Civilization. 8. Trauma, Denial, Recovery -- Pt. III. Art, Truth, and Humbug: The Search for Form and Meaning in a Commodity Civilization. 9. The Problem of Commercial Art in a Protestant Culture. 10. The Courtship of Avant-Garde and Kitsch. 11. The Pursuit of the Real. 12. The Things Themselves.
Includes index.
Includes bibliographical references.
Keywords: Advertising -- United States -- History -- 19th century; Advertising -- United States -- History -- 20th century